Kualifikasi Pendidikan SMA dan Standar Kerja Polri: Kajian Normatif Putusan MK No. 133/PUU-XXIII/2025 - Adi Ageng Rismoko; Mansyur, Abdul Rahman; Gita Sulika Sari (Indonesian Journal of Humanities and Social Sciences, 2025)
The discourse on elevating police recruitment qualifications to a Bachelor’s degree (S1) often overlooks the practical alignment between educational background and actual field workload. This study challenges the assumption that higher academic degrees equate to better operational readiness by critically evaluating the "Person-Job Fit" of High School (SMA) graduates against the dynamic workload specifications of the Indonesian National Police (Polri). Utilizing a qualitative case study of Constitutional Court Decision Number 133/PUU-XXIII/2025, this research synthesizes Workload Analysis to assess quantity demands and Competency Theory to validate foundational skills. The novelty of this research lies in re-conceptualizing the SMA diploma not as an academic deficiency, but as a sufficient "threshold competency" that ensures broad "talent pool" access and operational flexibility. The argument posits that while S1 degrees offer theoretical depth, the specific workload of entry-level police requires "trainability" and physical readiness found in SMA graduates. Findings indicate that the gap between raw SMA qualifications and professional demands is effectively bridged through the internal education system (Diktuk), which transforms these "threshold" inputs into "differentiating" professional outputs. Consequently, retaining the SMA requirement is a strategic necessity to balance the high volume of personnel needed for public service coverage with standardized competency development.